Inhibiting effect of shallow seed burial on grass weed emergence - Donato Loddo; Vasileios P. Vasileiadis; Roberta Masin; Maria C. Zuin; Giuseppe Zanin (Plant Protection Science, 2016)
The efficacy of superficial tillage as a sustainable tool to reduce the emergence of Digitaria sanguinalis, Setaria viridis, and Sorghum halepense was evaluated with field experiments. Seeds were buried at 1, 2, 5, and 10 cm of depth to simulate seed vertical distribution caused by autumn superficial tillage. Seedling emergence was monitored weekly for two years after sowing. The highest emergence was obtained in the first year after sowing and from 1 and 2 cm. Sorghum halepense was only slightly affected by seed burial, with 15% of emergence from 10 cm of depth, while D. sanguinalis was strongly affected, with 4% of emergence from 5 cm. The efficacy of superficial tillage as control tool could vary according to local weed flora.